Combining Statistical and Interpretative Analyses for Testing Readiness and IT Adoption Questionnaire. - Asrul, Sani; T.K.A, Rahman; Aang, Subiyakto; Ninuk, Wiliani (2019)
A questionnaire is one method that is very widely used for social research and is an essential stage in an information system survey in this case the instrument adopted from previous research. Research in the field of information systems today is highly developed by the context ranging from industry, education, and other areas that are not limited. The objectives of this study were to assess the nature of the psychometric properties of users, in this case, is the level of readiness of users in adopting information technology in SMEs. Respondents were chosen randomly and were active computer users in SMEs, and the questions and statements given could be responded to and understood well so that the perceptions between researchers and respondents were the same. The population used is by taking several SMEs industries in Jakarta. The survey was conducted by interviewing and distributing questionnaires to employees at SMEs. Data processing is done using partial least squares structural equation modeling (PLS-SEM). The results obtained are 13 of the 70 questions were recommended to be rejected. Besides, the findings can be used by other parties in terms of testing a questionnaire as a reference for consideration, and the confirmation results can be used as a reference in revising the questionnaire questions. Keywords: Statistical Analysis; Interpretative Analysis; SEM, Readiness and IT Adoption Questionnaire